Input subsidies to improve smallholder maize productivity in Malawi : Toward an African green revolution - Denning, G.L.; Kabambe, P; Sánchez, P.A.; Malik, A.; Flor, Rafael; Harawa, R.; Nkhoma, P; Zamba, C; Banda, C; Magombo, C; Keating, M; Wangila, J.; et al. (Public Library of Science, 2009)
Recent hikes in food prices have created economic and social turmoil in many African countries. But in Malawi, fertilizer and seed subsidies have enabled small-scale farmers to improve maize productivity and achieve food security.